Increasing Work Engagement Through Servant Leadership and Organizational Justice - Veronika Agustini Srimulyani (Universitas Negeri Yogyakarta, 2021)
Work engagement is important for teachers. Some factors that need to be considered by school management to improve work engagement are leadership practices and a climate of fairness in schools. This study aims to analyze how servant leadership and organizational justice practices affect the work engagement of permanent teachers at SMAK and SMKK in Cepu, Blora, and Rembang. Central Java. The research sample was 65 permanent teachers at SMAK and SMKK Cepu, Blora, and Rembang. The data analysis techniques used are simple linear regression and multiple linear regression, and the results showed that (1) servant leadership positively and significantly influenced organizational justice with a coefficient value of 0.655; (2) organizational justice positively and significantly affects work engagement with a coefficient value of 0.608; (3) Servant leadership does not significantly affect work engagement with a coefficient value of 0.009. The findings suggest that principals can select servant leadership practices to increase work engagement and build organizational justice, which includes distributive justice, procedural justice, and interactional justice.